2017
DOI: 10.3390/medicines4020034
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory, Antioxidant, Antibiotic, and Cytotoxic Activities of Tanacetum vulgare L. Essential Oil and Its Constituents

Abstract: Background: Tanacetum vulgare L. (Asteraceae) is a perennial herb that has been used to treat multiple ailments. Regional variability of the chemical composition of T. vulgare essential oils is well-known. Despite these regional chemotypes, most relevant studies did not analyze the complete chemical composition of the T. vulgare essential oil and its constituents in relation to their biological activities. Here, we assess the anti-inflammatory, antioxidant, antibacterial, and cytotoxic activities of T. vulgare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 39 publications
3
62
0
1
Order By: Relevance
“…In addition, β-caryophyllene exogenously added inhibited the mitochondrial ROS production in murine BV2 cells. 46 The reduced gluconeogenesis from L-lactate in the perfused livers of arthritic rats was already verified, including from other substrates, and it has been reported to occur due to lower activity of gluconeogenic key enzymes. The fact that no change occurred in the ROS production and respiration of isolated mitochondria (Figure 3) does not disprove that the phenomenon occurs in vivo because incubations of isolated organelles do not reproduce these conditions, as inflammatory mediators and β-caryophyllene, for example, are absent.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, β-caryophyllene exogenously added inhibited the mitochondrial ROS production in murine BV2 cells. 46 The reduced gluconeogenesis from L-lactate in the perfused livers of arthritic rats was already verified, including from other substrates, and it has been reported to occur due to lower activity of gluconeogenic key enzymes. The fact that no change occurred in the ROS production and respiration of isolated mitochondria (Figure 3) does not disprove that the phenomenon occurs in vivo because incubations of isolated organelles do not reproduce these conditions, as inflammatory mediators and β-caryophyllene, for example, are absent.…”
Section: Discussionmentioning
confidence: 94%
“…showed that the tested EO commercial aroma compounds (caryophyllene oxide, longifolene, nerolidol and davanone) inhibited the Gram‐positive bacteria. In fact, caryophyllene oxide is well‐known as preservative in food, drugs and cosmetics and was reported as responsible for the antibiotic activity of Tanacetum vulgare L. essential oil . Furthermore, Santos Patricia et al .…”
Section: Resultsmentioning
confidence: 99%
“…Se ha informado que el alcanfor es uno de los agentes antimicrobianos más eficientes de varias plantas (Magiatis et al, 2002). La actividad antibacteriana del alcanfor ha sido reportada previamente en la literatura (Gupta y Saxena, 2010;Sokovic et al, 2010;Hsouna et al, 2013;Coté et al, 2017), y se ha señalado que el mecanismo de acción del alcanfor sobre el crecimiento de microorganismos incluye la desestabilización de la estructura de la bicapa fosfolipídica, la interacción con las enzimas y proteínas de la membrana y su acción como intercambiador de protones que reduce el gradiente de pH a través de la membrana (Xu et al, 2005). Contrario a esto, Kotan et al (2007) encontraron que el alcanfor fue inefectivo como antibacteriano.…”
Section: Discussionunclassified